2023
DOI: 10.3892/br.2023.1699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung resection on heart structure and function: A tissue Doppler ultrasound survey of 43 cases

Jinfeng Chen,
Dongdong Song,
Zhiying Sun
et al.

Abstract: Changes in heart structure and function after lung resection in patients with lung cancer are challenging to manage. Therefore, a non-invasive and reliable measurement tool to gauge such changes is critical. The purpose of the present study was to compare cardiological changes before and after lung resection using tissue Doppler imaging (TDI). A total of 43 patients (19 men and 24 women) with primary non-small cell lung cancer (n=37) and metastatic cancer in the lungs (n=6) were enrolled in the study.nTDI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These differences did not reach statistical significance ( p = 0.115). A study by Chen et al [ 31 ] utilized tissue Doppler echocardiography (TDI) to assess cardiac changes before and after surgery in a group of 43 patients. The results showed that although certain structural parameters of the heart, such as the ascending aorta width and the anteroposterior diameter of the left atrium, significantly changed, cardiac functions remained stable, confirming that TDI is an effective tool for monitoring post-lung resection patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences did not reach statistical significance ( p = 0.115). A study by Chen et al [ 31 ] utilized tissue Doppler echocardiography (TDI) to assess cardiac changes before and after surgery in a group of 43 patients. The results showed that although certain structural parameters of the heart, such as the ascending aorta width and the anteroposterior diameter of the left atrium, significantly changed, cardiac functions remained stable, confirming that TDI is an effective tool for monitoring post-lung resection patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that although certain structural parameters of the heart, such as the ascending aorta width and the anteroposterior diameter of the left atrium, significantly changed, cardiac functions remained stable, confirming that TDI is an effective tool for monitoring post-lung resection patients. These findings are crucial for understanding how surgical interventions impact patients’ cardiac profiles and can help optimize postoperative management [ 31 ].…”
Section: Discussionmentioning
confidence: 99%